Predictive Maintenance in Industrial IoT Using Machine Learning Approach - Pani, Sasmita; Pattnaik, Omkar; Pattanayak, Binod Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Predictive maintenance utilising Machine learning approaches assist machines or systems in predicting and reducing various forms of machine failures using various particular strategies. Predictive maintenance (PdM) has developed as a crucial strategy to optimising maintenance procedures and enhancing industrial equipment dependability and efficiency. Predictive maintenance, which employs machine learning techniques, helps firms to proactively identify and handle possible equipment faults, decreasing unplanned downtime, lowering maintenance costs, and increasing operational productivity.